Tren Dakwah Digital : Membongkar Problem Media Sosial di Kalangan Da'i di Desa Silau Padang Kecamatan Sipispis Kabupaten Serdang Bedagai - Abror Ghufron; Anang Anas Azhar (JURNAL MANAJEMEN PENDIDIKAN DAN ILMU SOSIAL, 2024)
Fake news frequently spreads through comments and content shared by social media users, resulting in disinformation for the general public. These hoaxes not only concern general topics, but they also frequently address sensitive theological issues, which can cause misunderstanding and even conflict among believers. The purpose of this study is to identify and assess the challenges that preachers confront when using social media for da'wah in Silau Padang Village, Sipispis District, Serdang Bedagai Regency. The research approach employed is qualitative research, which describes facts through a series of phrases. This study employed a descriptive strategy. The descriptive method uses data from interviews with preachers in Silau Padang Village, Sipispis District, Serdang Bedagai Regency, as well. as data from books, journals, and other scholarly publications. The findings demonstrate that the trend of digital da'wah causes a variety of issues for da'i in Silau Padang Village. Some of them include rejection, disdain, and slander, which are frequently seen on social media platforms. Furthermore, the rapid advancement of technology allows for the rapid distribution of bad information and slander, which contradicts Islamic teachings that ban spreading other people's humiliation. Nonetheless, the da'i recognize that technology has enormous potential for spreading beneficial and constructive da'wah messages. To overcome these issues, preachers in Silau Padang Village employ a variety of tactics. They become innovative in observing the evolution of social media trends, mastering effective communication tactics, and responding to queries and comments from the community. They also use technological aspects such as live streaming and making da'wah content on prominent social media platforms. Based on the findings of this study, it can be stated that digital da'wah not only provides benefits, but also presents a number of problems that must be overcome. Understanding the difficulties and employing the appropriate tactics can help da'wah boost the success of their digital da'wah while also maintaining the purity of the da'wah message in the ever-changing social media environment.